ANALISIS HUKUM PENCEGAHAN TINDAK PIDANA PELECEHAN SEKSUAL DI LINGKUNGAN INSTITUSI PENDIDIKAN - Rahim, Rizki; Lahaling, Hijrah; Saharuddin, Saharuddin (Unisan Law Review, 2025)
This study aims to determine the regulation of the prevention of criminal acts of sexual harassment in educational institutions based on positive law, as well as the forms of prevention efforts. This study uses a normative research method with a law approach with a qualitative presentation model. The results of the study indicate that the legal regulation of preventing sexual harassment in educational institutions consists of the regulation of the prevention of sexual harassment through criminal law instruments, both the criminal law code and the child protection law, as well as through the regulation of the minister of education and culture as a technical instrument. Against prevention can be done in three forms, first; implementation of the Pre-Emptive function in the form of inculcating good general values ​​and norms in individuals, secondly; the implementation of the Preventive function in the form of the implementation of the third extension: is the internal efforts of Higher Education Institutions through an implosive approach. These results gave birth to recommendations in the form of the need to maximize enforcement, the need to hasten the issuance of the Law on the Protection of Victims of Sexual Violence, as well as to maximize the guidelines for interacting within the respective Education Units Keywords: Sexual Harassment Prevention, Sexual Harassment In College